The Correlation between Morphological Awareness and Vocabulary Mastery of The Fifth Semester Students of English Department of FKIP Universitas Riau - Nyayu Muharomah Arviyolla; Syofia Delfi; Dahnilsyah (UIR Press, 2022)
This research changed into meant to discover the. Correlation. between morphological. awareness. and. vocabulary., mastery. of the 5th semester. Students. of English, Department. of FKIP Universitas Riau. In this research, the research design was correlational design. Correlational is the types in. quantitative approach and the research, population was the, fifth semester. Students. of .English .Department of FKIP Universitas Riau. There are 39 students.from the 5th semester of English Department of FKIP Universitas Riau were selected and the sample was taken by using cluster random, sampling. The research instruments, of this study were morphological awareness test and vocabulary level, test. The data showed that 59.84 of frequency distribution mean score of morphological awareness were moderate level and 71.61 of frequency distribution mean score of vocabulary mastery were high vocabulary level. Additionally, the correlation coefficient was 0.601, which was on a scale from 0.00 - 1.00. The findings of this study indicated a positive, correlation between, two variables. According to this result, the correlation, between students' morphological, awareness and, their, vocabulary, mastery was classified as strong correlation. To facilitate students' understanding of the correlation, between, morphological awareness and vocabulary mastery, this, research would analyze the correlation between the two.